Strength and Chloride Content of Nanoclayed Ultra-High Performance Concrete - Mohd Faizal, Md Jaafar; Hamidah, M. S.; Muhd Norhasri, M. S. (2014)
The major cause for degradation of reinforced concrete due to chloride penetration has been the great research effort. A large number of published literatures on chloride penetration for ultra-high performance concrete have been reported. In this paper, the strength and the chloride resistance characteristic of the nanoclayed ultra-high performance concrete ( UHPC-NC ) were investigated. Series of ultra-high performance concrete specimens comprise of 0%, 1%, 3% and 5% of nanoclay replacing the total weight of cement were produced. Four ( 4) series of UHPC-NC specimens were designated as UHPC, UHPC-NC1, UHPC-NC3 and UHPC-NC5 respectively. The workability of fresh UHPC and UHPC-NCs, strength performance and chloride content of UHPC and UHPC-NCs measured using Mercuric Thiocyanate method were investigated. It is reported that all the UHPC mixes have high workability however; UHPC-NC5 recorded the lowest slump reading. It also clearly emerges that replacing 1% of cement with nanoclay enhance significantly the compressive and splitting tensile strength as compared to that without nanoclay. The optimum nanoclay replacement level was found to be 1% from the total weight of OPC for strength, but not for chloride diffusion. In term of total chloride content, it is revealed that the incorporation of nanoclay into UHPC mix leads to the reduction of chloride diffusion of the resulted UHPC. It shows that 5% replacement level of nanoclay effectively decreases the chloride diffusivity in UHPC.